2006
DOI: 10.1007/s11259-006-3434-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Aflatoxin and Ochratoxin A Production by Aspergillus Species in Poultry Feed Processing

Abstract: Poultry feeds are prone to fungal growth and mycotoxin production during processing. The identification of biota with the ability to produce mycotoxins is essential. The aims of this study were (1) to monitor the mycobiota counts at different stages of poultry feed processing; (2) to determine the occurrence of Aspergillus species; (3) to evaluate the natural incidence of aflatoxins and ochratoxin A. The ability of Aspergillus spp. and its teleomorphs isolated here to produce these toxins was also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 26 publications
9
33
2
1
Order By: Relevance
“…These results agree with those obtained by Rosa et al (2006) and Fraga et al (2007) who reported high percentages of A. flavus in poultry feed. Other studies from Argentina found Aspergillus section Flavi species and F. verticillioides as prevalent, followed by A. niger aggregate from poultry to pig feed (Gonzalez Pereyra et al 2008;Magnoli et al 1998).…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those obtained by Rosa et al (2006) and Fraga et al (2007) who reported high percentages of A. flavus in poultry feed. Other studies from Argentina found Aspergillus section Flavi species and F. verticillioides as prevalent, followed by A. niger aggregate from poultry to pig feed (Gonzalez Pereyra et al 2008;Magnoli et al 1998).…”
Section: Discussionsupporting
confidence: 93%
“…The genera most commonly associated with toxin production, which occur naturally, are Aspergillus, Penicillium and Fusarium (Fraga, Curvello, Gatti, Cavaglieri, & Dalcero, 2007;Kawashima, Vieira, & Soares, 2007;Paterson, Venâncio, & Lima, 2004). Ochratoxin has received more attention because, besides being suspected of causing cancer of the urinary tract and damage to kidneys (Pittet, 2001), it can be found in several foods such as coffee, cereals, wines, grapes for wine production, red paprika, dry fruits, beer and poultry feed processing (Almela et al, 2007;Burdaspal & Legarda, 1998;Chiodini, Scherpenisse, & Bergwerff, 2006;De Moraes & Luchese, 2003;Drusch & Ragab, 2003;Joosten, Goetz, Pittet, Schellenberg, & Bucheli, 2001;Palermo, Pietrobono, Palermo, & Rotunno, 2002;Serra, Mendonça, & Venâncio, 2006;Zimmerli & Dick, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In studies performed in Brazil, A. niger, A. sydowii, A. versicolor, A. ochraceus, A. melleus, A. alutaceus, and A. carbonarius species were isolated of corn and poultry feeds. A. ochraceus showed higher ability to produced OTA than other species isolated (Fraga et al 2007;Rosa et al 2006Rosa et al , 2009.…”
Section: Other Substratesmentioning
confidence: 82%
“…The mean levels detected ranged from 15 to 25 ng/g from three feeds. Fraga et al (2007) and Rosa et al (2006) detected that 100 % poultry corn-based feed samples were contaminated with OTA with levels from 17 to 197 ng/g and from 1.30 to 80 ng/g, respectively. Rosa et al (2009) observed on swine corn-based feeds that 44 % were positive for OTA contamination with levels between 42 and 224 ng/g.…”
Section: Impact Of Ochratoxin a Production By Aspergillus Section Nigmentioning
confidence: 99%